Analysis of the pulmonary function of motorcycle professional drivers and taxi drivers: the effect of air pollution. Prevention as the best way for caring - Sant’Anna Ferreira, Claudia Adriana; Lourenço dos Santos, Fernanda; Pereira da Costa, Ioli; Vanali Pereira, Luana; Beloto Lopes do Rego, Patrícia (O Mundo da Saúde, 2009)
The present study aims to analyze and to compare the pulmonary function of motorcycle professional drivers and taxi drivers of the city of São Paulo. 90 individuals divided in three sub-groups were evaluated: 30 motorcycle professional drivers (MG), 30 taxi drivers (TG) and 30 staff employees, the control group (CG). All were submitted to a pulmonary function test, with evaluation of forced vital capacity (CVF), forced expiratory volume in the first second (VEF1), relation CVF/VEF1 and expiratory flow from 25 to 75% (FEF 25-75%). Results show differences in all the variables regarding pulmonary function, with statistical differences among the groups. MG subjects presented the worse values. The highest difference was in FEF 25-75%, with averages of 98.8%, 78.7% and 65.4% respectively for CG, TG and MG, p< 0.001. We concluded that the group of motorcycle professional drivers presented a worse pulmonary function, which can be directly related to the intensity and time of exposure to pollutants